Diagnostic and prognostic role of hyperglycemia in acute phase of myocardial infarction - I. L. Telkova; R. S. Karpov (Кардиоваскулярная терапия и профилактика)
Aim. To study diagnostic and prognostic role of hyperglycemia in patients with acute phase of myocardial infarction (MI), according to five-year follow(up results. Material and methods. In total, 130 men aged 47,1±1,7 years were examined. In 75 patients, glucose level in venous blood was measured during acute MI phase, one week later, and after 21-26 days. Five(year follow-up data were available for 85,3% of the participants. Results. All patients were divided into two clinical groups (cG), according to glucose level in acute MI phase: cG I (n=43) and cG II (n=32), with glucose levels of 4,74±0,85 mM/l and 8,35±2,50 mM/l, respectively (p<0,00001). Five(year death rates in cG II and cG I were 66,6% and 48,6%, respectively (x2=2,79; p>0,05). Among patients with adverse outcomes, individuals with hypoglycemia during acute MI phase were prevalent (14,3% vs 7,1% in cG I). Maximal five(year survival was associated with isoglycemia and/or mild hyperglycemia. In patients with glucose level >7 mM/l, death HR was 1,56 (CI 1,14:3,46; p<0,05). For hypoglycaemia (<3,9 mM/l), death HR was maximal - 1,74 (CI 1,14:3,46; p<0,05). Conclusion. In acute MI phase, transitory hyperglycemia was registered in 44,4% of the patients, hypoglycemia – in 11,3%, and isoglycemia – in 44,3%. Hyper- and hypoglycemia were associated with aggravated clinical course, structural and metabolic myocardial disturbances, and adverse prognosis.